Stilpón z Megár medzi sokratikou a helenizmom - Jaroslav Cepko (Filozofia)
Ancient sources depict the so-called Megarian school in two seemingly contrasting ways: on the one hand, as eristic and dialectic, and on the other, as a continuation of the Socratic ethical orientation in philosophy. The figure of Stilpo of Megara serves as an outstanding example of how these two aspects complement and condition one another. This study focuses on the analysis of selected fragments, specifically Stilpo’s critique of non-tautological predication, as well as his response to criticisms concerning the immoral behavior of his daughter. Both cases are based on the premise that it is impossible to predicate “one thing of another.” Stilpo’s dialectical strategies, which challenge certain ontological and linguistic assumptions, thus also functioned as ethical exercises aimed at achieving inner stability. It makes him a bridge between Socratic inquiry and Stoic and Pyrrhonian philosophy and a key figure in the transition to the Hellenistic period.